Belief in Marriage The Evidence for Reforming Weddings Law - Probert, Rebecca (Bristol University Press, 2023)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence. This book draws on the accounts of 170 individuals who had, or led, a wedding ceremony outside the legal framework. The authors examine what these ceremonies can tell us about how couples want to marry, and what aspects of the current law preclude them from doing so.